Inequality in fetal autopsy in Canada - Auger, Nathalie; Tiandrazana, Rémi- Claude; Healy-Profitós, Jessica; Costopoulos, André (Journal of health care for the poor and underserved, 2016)
Purpose. Inequality in use of fetal autopsy is poorly understood, despite the importance of autopsy in establishing the cause of stillbirth for future prevention. We examined fetal autopsy rates between linguistic minorities in Quebec, Canada, and assessed trends over three decades. Methods. Using registry data on 11,992 stillbirths from 1981–2011, we calculated fetal autopsy rates for Francophones, Anglophones, and Allophones by decade. Results. We found lower fetal autopsy rates for Allophones (54.4%) than Francophones (68.5%) and Anglophones (63.4%), but rates decreased over time for all language groups. After 2000, Allophones had 25% higher risk of non-autopsy relative to Francophones, with 8.8 fewer autopsies for every 100 stillbirths. Allophones who were not autopsied had 32% higher risk of having an undetermined cause of death. Conclusion. Inequality in use of fetal autopsy may be widespread for minorities in Canada. Efforts to decrease stillbirth in minorities may require policies to increase autopsy rates.

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

La parole aux communautés : nous sommes là! La vitalité des communautés de langues officielles en situation minoritaire. Rapport du Comité permanent des langues officielles - Lauzon, Guy (Gouvernement du Canada, Chambre des communes 39e Législature, 1er session, 2007)

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda, R.; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.